2013
DOI: 10.1038/nature12870
|View full text |Cite|
|
Sign up to set email alerts
|

DWARF 53 acts as a repressor of strigolactone signalling in rice

Abstract: Strigolactones (SLs) are a group of newly identified plant hormones that control plant shoot branching. SL signalling requires the hormone-dependent interaction of DWARF 14 (D14), a probable candidate SL receptor, with DWARF 3 (D3), an F-box component of the Skp–Cullin–F-box (SCF) E3 ubiquitin ligase complex. Here we report the characterization of a dominant SL-insensitive rice (Oryza sativa) mutant dwarf 53 (d53) and the cloning of D53, which encodes a substrate of the SCFD3 ubiquitination complex and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
822
5
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 708 publications
(880 citation statements)
references
References 48 publications
(70 reference statements)
32
822
5
4
Order By: Relevance
“…Among these and other phytohormones, the activation of the signalling pathways of GA, jasmonic acid and strigolactone also utilize a derepression mechanism by the proteasomal degradation of specific repressors in a manner similar to that of auxin [44][45][46][47][48] . Interestingly, a GA-insensitive dwarf (gaid) mutant of wheat was characterized to be insensitive to exogenous GA, correlated to the elevated levels of the GA signalling repressor Rht/DELLA protein and a putative cyclophilin TaCYP20-2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Among these and other phytohormones, the activation of the signalling pathways of GA, jasmonic acid and strigolactone also utilize a derepression mechanism by the proteasomal degradation of specific repressors in a manner similar to that of auxin [44][45][46][47][48] . Interestingly, a GA-insensitive dwarf (gaid) mutant of wheat was characterized to be insensitive to exogenous GA, correlated to the elevated levels of the GA signalling repressor Rht/DELLA protein and a putative cyclophilin TaCYP20-2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…GR24 can induce an interaction between D14 and D3, which has been shown in cells by yeast 2-hybrid analysis [25] and in extracts by pull-down assays [19,20]. To test whether GR24 directly stimulates an interaction between D14 and D3 in vitro, and to quantitatively analyze such an interaction, we used highly purified recombinant proteins in an AlphaScreen luminescence proximity assay.…”
Section: Binding Of Gr24 Inside Of the D14 Lbp Is Required For The Inmentioning
confidence: 99%
“…Recent studies have identified the putative transcriptional repressor D53 [19,20] as well as the transcription factor BES1 as SCF D3 substrate targets in response to SL exposure and the D53 paralog SMAX1 in response to karrikin exposure. SLs induce association of D14 with D3/D53 and D3/BES1 complexes and promote SCF D3 -mediated degradation of D53 [19,20], BES1 [21], and D14 itself [22].…”
Section: Introductionmentioning
confidence: 99%
“…SL degrades the D53 protein in rice [4,5] and the related SMXL6, SMXL7 and SMXL8 proteins in Arabidopsis [1]. D53 directly prevents the transcriptional activation function of IPA1 (OsSPL14) in rice [2] and the related SPL3 and SPL17 proteins in wheat [8]; D53 prevents IPA1 upregulation of D53 gene expression in rice [2], and TaSPL3 upregulation of TaTB1 gene expression in wheat [8].…”
mentioning
confidence: 99%
“…This interaction with D53 prevented the transcriptional activation activity of IPA1 in a dose-dependent manner (Figure 1). In rice, D53 is one of the only known transcriptional targets of SL [4,5], and D53 prevented IPA1 from upregulating D53 expression [2] ( Figure 1). By showing evidence of a mechanism via which SL signaling transcriptionally regulates downstream target genes, this work has enabled description of a continuous SL signaling pathway from perception to gene regulation ( Figure 1).…”
mentioning
confidence: 99%